HOTS & Problem-Based Learning (PBL) with blended learning - Laili Mei Sulistiyani; Habiddin Habiddin; Yahmin Yahmin (J-PEK (Jurnal Pembelajaran Kimia), 2022)
In the world of education, attainment of competence does not only involve increasing knowledge but must be equipped with creative abilities, high-level thinking, strong character, and supported by the ability to utilize information and communication. One way to achieve these competencies is by using blended learning-based problem-based learning methods. This study seeks to review articles on improving students' higher-order thinking skills using blended learning based on problem-based learning methods to investigate the combination of these two methods in increasing students' HOTS.